Immigration Policymaking in the Global Era - Duncan, N. author. aut Link
XIII, 176 p.
Keywords: Through a comparative case study analysis of the United Kingdom and Germany, with references to the United States, this study examines the impetuses for and processes by which governments came to choose the points system for immigration control.